A coupled THMC modeling application of cemented coal gangue-fly ash backfill. (15th January 2018) - Wu, Di; Deng, Tengfei; Zhao, Runkang
Highlights: We develop a THMC model to analyze the coupled thermo-hydro-mechanical-chemical behavior of CGFB. The developed model can analyze the temperature, pore water pressure, water drainage, lateral pressure, as well as stress-strain development of hydrating CGFB. This study can contribute to a better design of stable, durable and environment-friendly CGFBs. Abstract: Cemented coal gangue-fly ash backfill (CGFB) is prepared by mixing coal gangue, fly ash, cement and water. The CGFB mixtures are filled into mined-out areas of coal mines for ground control and waste disposal. Once placed underground, the performance of CGFB is subjected to the thermal (T), hydraulic (H), mechanical (M) and chemical (C) processes and THMC coupling effects. Understanding the coupled THMC influence on CGFB is crucial for predicting the behavior of CGFB. This paper develops a THMC coupling model to describe and analyze the coupled THMC processes that occur in CGFB. The developed model considers the courses of thermal conduction and convection, fluid flow, suction development, chemical shrinkage, thermal expansion, and binder hydration. The simulation and prediction results of the developed model are compared with the experimentally tested data from 3 case studies. Good agreement is found between the modeling results and experimental data, validating the capability of the developed model to well characterize the properties of CGFB under coupled THMC loadings. The modeling results can also contribute to a better design of stable, durable and environment-friendly CGFB structures.